Partitioning of soil phosphorus among arbuscular and ectomycorrhizal trees in tropical and subtropical forests - Xubing Liu; David F. R. P. Burslem; Joe D. Taylor; Andy F. S. Taylor; Eyen Khoo; Noreen Majalap‐Lee; Thorunn Helgason; David Johnson (Ecology Letters, 2018)
Partitioning of soil phosphorus (P) pools has been proposed as a key mechanism maintaining plant diversity, but experimental support is lacking. Here, we provided different chemical forms of P to 15 tree species with contrasting root symbiotic relationships to investigate plant P acquisition in both tropical and subtropical forests. Both ectomycorrhizal ( ECM ) and arbuscular mycorrhizal ( AM ) trees responded positively to addition of inorganic P, but strikingly, ECM trees acquired more P from a complex organic form (phytic acid). Most ECM tree species and all AM tree species also showed some capacity to take up simple organic P (monophosphate). Mycorrhizal colonisation was negatively correlated with soil extractable P concentration, suggesting that mycorrhizal fungi may regulate organic P acquisition among tree species. Our results support the hypothesis that ECM and AM plants partition soil P sources, which may play an ecologically important role in promoting species coexistence in tropical and subtropical forests.